2021
DOI: 10.18844/cjes.v16i4.6055
|View full text |Cite
|
Sign up to set email alerts
|

A description and factors causing student anxiety during the COVID-19 pandemic in indonesia

Abstract: Abstract- This study aims to determine the level and factors that cause student anxiety during the Covid-19 pandemic. Respondents in this study were 1.013 students from five universities in three provinces in Indonesia, i.e., Lampung, Special Region of Yogyakarta, and South Sulawesi. The data were collected from 24th to 29th of April 2020. The data were obtained using a Covid-19 anxiety survey and a questionnaire about the factors causing student anxiety, which were distributed by utilizing google form. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In e-learning environment it's difficult to carry out that role because of the limit direct interaction between lectures and students. Lecturer can facilitate the students easily in face-to-face learning, but in e-learning situations tend to lack of essential guidance for students [12].…”
Section: Instructor Dimensionmentioning
confidence: 99%
“…In e-learning environment it's difficult to carry out that role because of the limit direct interaction between lectures and students. Lecturer can facilitate the students easily in face-to-face learning, but in e-learning situations tend to lack of essential guidance for students [12].…”
Section: Instructor Dimensionmentioning
confidence: 99%
“…Coronavirus disease was first named as severe acute respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and later named by the World Health Organization as 2019 Novel Coronavirus Disease (2019-nCoV) or COVID-19 [1], [2]. Researchers found out that health [3], psychological [4], economic [5] are the major aspects of life that academic stakeholders experienced during the pandemics [6]- [11]. Bickley et al [12] confirmed the education sectors were challenged in the new normal, especially the home-based and online learning process.…”
Section: Introductionmentioning
confidence: 99%